What specifically contributes to disturbed non-verbal fluency in patients with bipolar disorder: Ineffective performance initiation, slowed processing or lack of the execution strategy?. (January 2019) - Krukow, Paweł; Harciarek, Michał; Grochowski, Cezary; Makarewicz, Agata; Jonak, Kamil; Karakuła-Juchnowicz, Hanna
Highlights: Non-verbal fluency is an important part of speed-dependent executive functions domain. The determinants of design fluency in bipolar disorder has not been studied so far. Poor outcomes of design fluency in BD patients were predicted by performance slowing. Design fluency in controls group was explained only by executive strategy indicators. Cognitive slowdown in a bipolar group was associated with residual depressive symptoms. Abstract: The study aimed at identifying the cognitive and clinical determinants of impaired design fluency in bipolar patients, with special reference to processing speed and performance strategy. A sample of bipolar disorder patients (BD, n  = 45) and matched healthy controls (HC, n  = 42) underwent the assessment of figural fluency, cognitive and manual speed, cognitive effort and affective state. An electronic version of design fluency test was applied, enabling assessment of performance speed, execution strategy and spontaneous fluctuations in production efficiency. Additional clinical variables were also controlled. BD patients produced significantly less unique designs, performed slower, utilized less effective strategy, their ability to concentrate designs production in the initial phase of performance was significantly reduced compared with HC. Regression analysis revealed that in BD patients design fluency main outcome was significantly predicted by slowed creation of designs and the number of hospitalizations, while in the HC group, the main fluency result was predicted only by the executive strategy indicators. Our study showed that non-verbal fluency in BD group was determined by essentially different neuropsychological functions than in healthy controls. Obtained findings confirm that cognitive slowdown should be an important goal of cognitive remediation and pharmacological interventions in bipolar disorder.